The improvement of the social conditions of country life - Bolton, James Courtney (My University, 1899)
Introduction: Before we take up the improvement of country life, let us take a look at the conditions at present. The social standing if the farmer is rather low at present. The social standing of the farmer is rather low at present although it is improving somewhat. We all know of the drift of people from the farm to the city, and often those that do not go wish they could because they have such poor society where they live. Let us see what causes this flow of people to the cities, and this poor social condition of country life. There are several theories why people are drifting from the country to the city. One is that people are getting out of employment on account of machinery that is now used on the farm. Another claim is that the social condition of the city is so much superior to that of the country.
Citation: Bolton, James Courtney. The improvement of the social conditions of country life. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Improved Roads; Less Expense Shipping; More social Interaio; Theses; Manuscripts (documents)